ANALYSIS OF THE SELF-SUFFICIENCY OF WHEAT PRODUCTION IN BOSNIA AND HERZEGOVINA - Ivanišević, Marko; Popov, Tatjana; Gvozden Sliško, Dijana (Bulletin of Natural Sciences Research, 2024)
Wheat is recognized as a crucial staple food across nearly all countries. Achieving a specific level of self-sufficiency in primary food products is a common objective for nations, aimed at safeguarding domestic production, minimizing dependency on imports, and mitigating disruptions in global and regional supply chains. This study provides an analysis of wheat production and yields in Bosnia and Herzegovina, with the goal of evaluating the self-sufficiency of wheat production. The analysis covers the period from 2010 to 2019. The study places particular emphasis on spatial analysis, including production, yield, and self-sufficiency at the level of local administrative units. The findings indicate that Bosnia and Herzegovina’s self-sufficiency in wheat production stands at 54%, with significant variability in production quantities across different local government units. These insights offer a foundation for future research that could delve deeper into the spatial-temporal, economic, and food security dimensions of wheat production.